Effectiveness of diabetes self-management education (DSME) in type 2 diabetes mellitus (T2DM) patients: Systematic literature review - Ucik Ernawati; Titin Andri Wihastuti; Yulian Wiji Utami (SAGE Publishing, 2021)
Diabetes mellitus is a chronic disease characterized by high glucose levels (hyperglycemia) due to metabolic disorders that prevent patients from producing sufficient amounts of insulin. This research aims to test the effectiveness of implementing diabetes self-management education in patients with Type 2 diabetes mellitus. The search for relevant articles was carried out through Google Scholar, PubMed, Proquest, and Science Direct using the keywords diabetes mellitus, management education, self-care, diabetes self-management education, DSME, T2DM. The articles were then selected based on inclusion and exclusion criteria. Furthermore, the data were extracted, grouped, and concluded. Based on 15 articles, diabetes self-management education intervention provides significant effectiveness to lifestyle changes and the self-care of T2DM patients. In conclusion, diabetes self-management education intervention has been shown to be effective in dealing with type 2 diabetes mellitus. Furthermore, DSME has a positive effect on lifestyle changes and the self-care of T2DM patients.